EFFECTIVENESS OF THE SIAP KERJA APPLICATION PROGRAM AT THE MANPOWER OFFICE (DISNAKER) OF SIDOARJO REGENCY - Oktaviani, Miftahul Hidayati; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to describe and analyze the effectiveness of the Siap Kerja application program developed by the Sidoarjo Regency Manpower Office to support the community in accessing job opportunities and preparing for the labor market. Method: A qualitative approach was employed with data collected through interviews and observations, focusing on program implementation and its impact on employment. Results: The findings show that the program effectively facilitates job seekers in finding vacancies, thereby contributing to reducing the unemployment rate in Sidoarjo Regency. Program socialization is conducted primarily online through social media platforms such as Instagram, while monitoring and evaluation are carried out via user complaints and periodic reviews. The results also indicate that the application not only improves access to employment opportunities but also strengthens public trust in digital-based manpower services. Novelty: This research highlights the innovative application of digital technology in addressing employment issues at the regional level, demonstrating how local government initiatives can leverage online platforms to enhance labor market efficiency and inclusivity, particularly in reducing unemployment through accessible and community-oriented solutions.